Expression of PD-L1 and p-RPS6 in epithelial dysplasia and squamous cell carcinoma of the oral cavity - Hanroongsri, Jaruwat; Amornphimoltham, Panomwat; Younis, Rania H.; Chaisuparat, Risa (Frontiers in Oral Health, 2024)
Introduction Oral squamous cell carcinoma (OSCC) is often preceded by oral epithelial dysplasia (OED). The role of ribosomal protein S6 (RPS6) and programmed cell death ligand-1 (PD-L1) in the progression of OED to OSCC remains unclear. This study aimed to investigate the expression of phosphorylated RPS6 (p-RPS6) and PD-L1 in OSCC and OED and to examine its relationship with clinicopathological features. Methods Fifty-two OSCC and 48 OED cases were recruited for immunohistochemical analysis of p-RPS6 and PD-L1 expression. The expression of markers was correlated with clinicopathological features of OSCC and OED. Results We found p-RPS6 expression in all cases of OSCC and OED, whereas PD-L1 was expressed in 42/48 (87%) OED and in 28/52 (53%) OSCC. The patients with mild OED presented higher expression level of PD-L1 and p-RPS6 significantly, when compared to moderate-differentiated OSCC patients (p < 0.05). Moreover, we found a significant positive correlation between PD-L1 and p-RPS6 expression in OED and OSCC patients (p < 0.01). The PD-L1 expression was significantly related to more than 2 cm tumor size in OSCC patients (p = 0.007). Discussion Our findings suggest the upregulation of PD-L1 may be related with activation of the mTOR pathway in the early events of tumor progression and the pathogenesis of OSCC.